2011
DOI: 10.1073/pnas.1100629108
|View full text |Cite
|
Sign up to set email alerts
|

Repair of injured proximal tubule does not involve specialized progenitors

Abstract: Recently we have established that the kidney tubular epithelium is repaired by surviving epithelial cells. It is not known, however, whether a population of intratubular adult progenitor cells are responsible for this epithelial repair after acute kidney injury. In this study, we used an unbiased DNA analog-based approach that does not rely on candidate markers to track multiple rounds of cell division in vivo. In the proximal tubule, robust thymidine analog incorporation was observed postinjury. Cell division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
269
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(297 citation statements)
references
References 38 publications
(46 reference statements)
15
269
2
2
Order By: Relevance
“…However, during AKI, repair of epithelial cells mostly depends on cells directly derived from the migration and proliferation of adjacent tubular epithelial cells [1,2]. In addition, a recent study in rodents demonstrated that proliferation of regenerating tubular epithelium following acute ischemic injury is stochastically distributed among surviving tubular cells [25]. However, the existence of a scattered population of CD133þCD24þ tubular-committed progenitors that is highly resistant to death induced by toxic agents is consistent with this observation.…”
Section: Discussionsupporting
confidence: 56%
“…However, during AKI, repair of epithelial cells mostly depends on cells directly derived from the migration and proliferation of adjacent tubular epithelial cells [1,2]. In addition, a recent study in rodents demonstrated that proliferation of regenerating tubular epithelium following acute ischemic injury is stochastically distributed among surviving tubular cells [25]. However, the existence of a scattered population of CD133þCD24þ tubular-committed progenitors that is highly resistant to death induced by toxic agents is consistent with this observation.…”
Section: Discussionsupporting
confidence: 56%
“…Remarkably, during AKI, the normally quiescent renal tubular cells reenter the cell cycle (29)(30)(31)(32)(33)(34), and blocking cell-cycle progression can reduce renal injury (28). Here, we provide evidence that the CDK4/6 pathway is activated early during AKI and demonstrate significant protective effects of CDK4/6 inhibitors in animal models of cisplatin-induced AKI.…”
mentioning
confidence: 64%
“…However, the major etiology of AKI is renal tubular cell death caused by ischemia, infections, or drug-induced toxicities (44)(45)(46)(47). During AKI, along with cell death, cell-cycle activation is initiated in the normally quiescent renal tubular cells (29)(30)(31)(32)(33)(34). It is believed that this proliferative response may contribute to tissue regeneration (28,32,33,38), although this notion has been challenged recently (48).…”
mentioning
confidence: 99%
See 2 more Smart Citations